Politeness Principle in 2008 Presidential Debates between Mc Cain and Obama - Pakzadian, Maryam (Mediterranean Journal of Social Sciences, 2012)
This paper discusses â€œdiplomatic languageâ€ with reference to linguistic theories, especially theories of pragmatics involving thePoliteness Principle. In this paper the researcher tries to investigate the 3 presidential debates in 2008 between Senator Mc Cain andObama. After checking the accuracy of transcripts against the videotape, the researcher through sentence by sentence analysis of thetext, examines to what extent each candidate contributes more to Leech politeness maxims. The results of the paper show that in allthree debates incident of maxim contribution is preceded by Obama. The researcher closes the paper with discussing the positive impactof these 6 maxims in face saving and group connectedness. She points to politeness maxims consideration as one of having crucialimportance which helps diplomatic language to be more effective and successful.